(untitled) (Global Journal of Medical Research, 2022)
Malaria has been a major public health problem in India with cases therein contributing significantly to the overall malaria burden within South East Asia Majority of malaria cases in India have occurred within the eastern and central regions of the country Over 80 of the country s total malaria cases have been reported from 10 states Statistics for the state of West Bengal had reported approximately 26 000 and 25 000 malaria cases in 2014 and 2018 respectively with Kolkata still being considered the most malaria-prone district of West Bengal